About the Status of Law Norms - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2021)
This article analyzes the problem of recommendatory norms in Russian literature, both Soviet and modern, which is solved ambiguously. As for Soviet theoretical scientists, recommendation norms were the subject of study by such authors as Nikolai Grigorievich Alexandrov, Alexander Filippovich Shebanov, Peter Yemelyanovich Nedbailo, Vladimir Srgeevich Petrov, Valery Evaldovich Krasnyansky. Viktor Mikhailovich Gorshenev, Cecilia Abramovna Yampolskaya, Vladimir Matveevich Solyanik, Viktor Lavrenievich Kulapov, whose scientific works are given below. Regarding modern legal literature, unfortunately, we have to state that, basically, with rare exceptions (scientific articles by Vladimir Valentinovich Kozhevnikov, Alexander Evgenievich Kondratyev, Sadri Salikhovich Kuzakbirdiev), this problem is considered only in educational literature. When preparing a scientific article, the following methods were used: general philosophical (dialectical-materialistic), which is used in all social sciences; general scientific (analysis and synthesis, logical and historical, comparisons, abstractions, etc.), which are used not only by the theory of state and law, but also by other social sciences; special methods (philological, cybernetic, psychological, etc.), developed by special sciences and widely used for the knowledge of state and legal phenomena; private scientific (formal legal, interpretation of law, etc.), which are developed by the theory of state and law. Soviet scientists - legal theorists: supporters and opponents of the recognition of recommendatory norms of law. From the point of view of scientists, a